The Role of the Green Supply Chain in Steering the Company Towards Green Marketing (American Journal of Economics and Business Innovation, 2025)
The green transition is receiving increasing attention both in research and professional practice. The relationship between the green supply chain and green marketing is critically important for organizations aiming to enhance green practices. The objective of this paper is to explore the relationship between the green supply chain and green marketing within the State Company for Electrical and Electronic Industries in Iraq. The survey included 80 participants from senior management levels across the company’s geographically dispersed branches, along with specialists in supply chain management and marketing. A quantitative approach was adopted to analyze and present the study’s findings. The key result of the study indicates a significant impact of the green supply chain on green marketing, primarily through green purchasing, packaging, and distribution. In contrast, green design and manufacturing did not exhibit a statistically significant effect. The current paper highlights the emerging nature of green practices in Iraq and interprets the findings within this context. Additionally, it provides a practical guide for professionals in heavy industries, illustrating the relationship between the green supply chain and green marketing.